Study on response characteristics of grid‐side converter controller of PMSG to sub‐synchronous frequency component. Issue 7 (30th May 2017) - Bi, Tianshu; Li, Jingyi; Zhang, Peng; Mitchell‐Colgan, Elliot; Xiao, Shiwu
Abstract : Multiple sub‐/super‐synchronous frequency components were detected when sub‐synchronous oscillation (SSO) occured in permanent magent synchronous generator (PMSG)‐based wind farm in Northwest China. This caused three 600 MW turbine generators to trip because of torsional oscillation of the shaft. Then for one year, for eliminating the multiple frequency components, the relevant wind farms have been tripped for 111 times. The tripped wind power sometimes could even be up to 300 MW. However, the multiple frequency components' producing mechanism is still not clear. This study explains the mechanism by analysing the response characteristics of grid‐side converter (GSC) controller to the sub‐synchronous frequency component. When a sub‐synchronous frequency component is fed into GSC controller as an input signal, the expression for the output signal is derived. Furthermore, the frequency transformation relationship between input and output signals, the amplitudes of multiple frequency components in output signals are all discussed in detail. The theoretical analysis is then validated by the simulation results and the on‐site data measured by the phasor measurement unit (PMU). With the theoretical analysis, the main frequency components which should be suppressed are determined. The multiple frequency components can be mitigated not by tripping wind farms any more. This is conducive to the accommodation of renewable energy.